The impact of future time perspective on academic achievement: Mediating roles of academic burnout and engagement - Shuai Hong (PLoS ONE, 2025)
Future time perspective is closely related to students’ academic achievement, potentially affecting academic achievement through academic emotions. This study examines the relationship between future time perspective and academic achievement, exploring the mediating roles of academic burnout and academic engagement among 686 university students. Using a cross-sectional quantitative design, we investigated both the direct relationship between future time perspective and academic achievement, and the indirect effects mediated by burnout and engagement. Structural equation modeling revealed that future time perspective predicts academic achievement directly, and also indirectly through increasing academic engagement and reducing academic burnout. Notably, the mediating effect of academic burnout was found to be more significant than that of academic engagement. Overall, the results highlight the crucial role of future time perspective and its mediating mechanisms in promoting academic success, suggesting potential interventions to enhance students’ future orientation and academic well-being.